Psychometric Properties of a Neuropsychological Assessment Scale for Diagnosing Alzheimer's Disease in the Illiterate and Low-Educated Subjects in Iran - Ameneh Ahmadi; Maryam Noroozian; Mohsen Kachooei; Zahra Hooshyari; Aram Golsokhan (Iranian Journal of Psychiatry)
Objective: Because of changes in the population structure over time, dementia is one of the main concerns of the health systems worldwide. Screening for dementia in primary care settings, especially among high-risk populations, is essential. The aim of this study was to design, develop, and evaluate the reliability and validity of a diagnostic scale for Alzheimer's disease tailored to low-educated and illiterate populations. Method: This study, conducted at Roozbeh Psychiatric Hospital and Yaadmaan Institute for Brain Cognition and Memory Studies, utilizes a mixed-methods approach for collecting, analyzing, and interpreting the data. Once the questionnaire was confirmed to be clear, appropriate, and consistently presented, it was administered to a purposive sample of 250 patients selected based on the study's specific inclusion criteria. These patients underwent a comprehensive neuropsychological assessment, which included the Behavioral Pathology in Alzheimer's Disease Rating Scale (BEHAVE-AD), The Katz Activities of Daily Living Scale (Katz ADL) and The Functional Assessment Staging Tool (FAST). The scale construction process was conducted in four phases. Results: Confirmatory factor analysis showed that all questions significantly loaded on their respective factors, effectively measuring their intended constructs. The root mean square error of approximation (RMSEA) was less than 0.08, indicating a good model fit and supporting the scale's validity. The Adjusted Goodness of Fit Index (AGFI) and Goodness of Fit Index (GFI) were near 0.9, while the Comparative Fit Index (CFI), Normed Fit Index (NFI), Non-Normed Fit Index (NNFI), and Incremental Fit Index (IFI) exceeded 0.9. Correlational analysis with the FAST, Activities of Daily Living (ADL), and BEHAVE-AD scales confirmed significant relationships, validating the scale's convergent and divergent validity. The overall reliability, measured by Cronbach’s alpha coefficient, was 0.96, indicating excellent internal consistency, with subdomain reliability coefficients ranging from 0.7 to 0.88. Conclusion: The diagnostic scale for Alzheimer's disease demonstrates adequate fit and construct validity for assessing cognitive impairments in low-educated and illiterate patients across the 12 domains of orientation, judgment, abstract thinking, similarity, verbal fluency, repetition, working memory, visual-spatial skills, calculation, executive function, prosopagnosia, and naming. This culturally and linguistically adaptable assessment addresses gaps in diagnostic tools for low-literacy populations, enabling accurate evaluations of dementia and facilitating early diagnosis and treatment. The findings enhance existing knowledge by providing a reliable tool for early Alzheimer's diagnosis among low-literacy groups. However, further research is needed to validate the scale across diverse ethnic backgrounds and geographical locations to ensure its relevance and sensitivity to various contexts.